Representasi Makna Kata “Monster” dalam Sudut Pandang Orangtua dan Guru pada Film Monster: Analisis Semiotika Arnold Barthes - Eka Lestari; Abdul Khohar; Farida Hariyati (J-CEKI : Jurnal Cendekia Ilmiah, 2024)
This research aims to find out the meaning of the word "monster" from the perspective of parents and teachers in the movie Monster by Hirokazu Kore-oda. The approach method used in this study is a qualitative descriptive research method. Using the semiotic analysis method by Roland Barthes which consists of the order of signification, namely denotation and connotation. The results of this research show that the meaning of the word "monster" represents other people's views on other human behaviors and traits. Saori as a single mother said the dialogue "you don't have a human heart" to the teachers, referring to the meaning of the word "monster". This meaning is taken from Saori's point of view on the behavior shown by the school, they are silent without providing information related to violence against children at school. Likewise, teachers say "monster" which refers to the behavior and nature of students' parents. Teachers think that parents of students are chatty and can adverse the school's reputation. The occurrence of misunderstandings in communication resulting in conflicts and differences in perception that lead to negative assumptions about others.